Assessing inbred-hybrid relationships for developing drought tolerant provitamin A - quality protein maize hybrids - Obeng-Bio, E.; Badu-Apraku, Baffour; Ifie, B.E.; Danquah, A.; Blay, E.T.; Dadzie, M.A. (Wiley, 2020)
Drought tolerant early maturing maize (Zea mays L.) inbred lines with high levels of provitamin A and quality protein (PVA‐QPM) are urgently needed for development of superior hybrids to mitigate malnutrition and intensify maize production and productivity in sub‐Saharan Africa (SSA). This study was designed to (1) identify early maturing inbred lines with combined tolerance to drought, elevated tryptophan and PVA contents, (2) examine inbred‐hybrid relationships for tryptophan and PVA accumulation, and (3) select hybrids with outstanding grain yield performance. A total of 64 inbred lines and six checks, plus 96 hybrids and four checks were evaluated under drought and well‐watered environments in Nigeria for two years. Eighteen parental lines and 54 derived hybrids were assayed for tryptophan and PVA contents. Ten drought tolerant inbred lines with high tryptophan and elevated PVA levels were identified in the top 10 hybrid combinations across managed drought and well‐watered conditions. Inbred‐hybrid relationship was significant for grain yield under each and across the two contrasting environments. Significant average heterosis were found for tryptophan and PVA under well‐watered conditions. This indicated that the selected inbred lines could be utilized for developing high yielding PVA‐QPM hybrids tolerant to drought stress in SSA. The 10 top‐performing PVA‐QPM hybrids identified are being extensively evaluated in multi‐locations and subsequently in on‐farm trials for commercialization throughout SSA.